CD133 Is a Marker For Long-Term Repopulating Murine Epidermal Stem Cells - Charruyer, A (2012)
Maintenance, repair and renewal of the epidermis are thought to depend on a pool of dedicated epidermal stem cells. Like for many somatic tissues, isolation of a nearly pure population of stem cells is a primary goal in cutaneous biology. We used a quantitative transplantation assay, using injection of keratinocytes into subcutis combined with limiting dilution analysis, to assess the long-term repopulating ability of putative murine epidermal stem populations. Putative epidermal stem cell populations were isolated by FACS sorting. The CD133(+) population and the subpopulation of CD133(+) cells that exhibits high mitochondrial membrane potential (DΨm(hi)), were enriched for long-term repopulating epidermal stem cells vs. unfractionated cells (3.9 and 5.2-fold, respectively). Evidence for self-renewal capacity was obtained by serial transplantation of long-term epidermal repopulating units derived from CD133(+) and CD133(+)ΔΨm(hi) keratinocytes. CD133(+) keratinocytes were multipotent and produced significantly more hair follicles than CD133(−) cells. CD133(+) cells were a subset of the previously described integrin α6(+)CD34(+) bulge cell population and 28.9±8.6% were label retaining cells. Thus, murine keratinocytes within the CD133(+) and CD133(+)ΔΨm(hi) populations contain epidermal stem cells that regenerate epidermis for the long-term, are self-renewing, multipotent, and label-retaining cells.